Pre‐drill Groundwater Geochemistry in the Karoo Basin, South Africa. Issue 2 (30th January 2018) - Harkness, Jennifer S.; Swana, Kelley; Eymold, William K.; Miller, Jodie; Murray, Ricky; Talma, Siep; Whyte, Colin J.; Moore, Myles T.; Maletic, Erica L.; Vengosh, Avner; Darrah, Thomas H.
Abstract: Enhanced production of unconventional hydrocarbons in the United States has driven interest in natural gas development globally, but simultaneously raised concerns regarding water quantity and quality impacts associated with hydrocarbon extraction. We conducted a pre‐development assessment of groundwater geochemistry in the critically water‐restricted Karoo Basin, South Africa. Twenty‐two springs and groundwater samples were analyzed for major dissolved ions, trace elements, water stable isotopes, strontium and boron isotopes, hydrocarbons and helium composition. The data revealed three end‐members: a deep, saline groundwater with a sodium‐chloride composition, an old, deep freshwater with a sodium‐bicarbonate‐chloride composition and a shallow, calcium‐bicarbonate freshwater. In a few cases, we identified direct mixing of the deep saline water and shallow groundwater. Stable water isotopes indicate that the shallow groundwater was controlled by evaporation in arid conditions, while the saline waters were diluted by apparently fossil meteoric water originated under wetter climatic conditions. These geochemical and isotopic data, in combination with elevated helium levels, suggest that exogenous fluids are the source of the saline groundwater and originated from remnant seawater prior to dilution by old meteoric water combined with further modification by water‐rock interactions. Samples with elevated methane concentrations (>14 ccSTP/kg) were strongly associated with the sodium‐chloride water located near dolerite intrusions, which likely provide a preferential pathway for vertical migration of deeply sourced hydrocarbon‐rich saline waters to the surface. This pre‐drill evaluation indicates that the natural migration of methane‐ and salt‐rich waters provides a source of geogenic contamination to shallow aquifers prior to shale gas development in the Karoo Basin. Abstract : Article impact statement : This study evaluates the sources of salinity and hydrocarbon gases in Karoo Basin groundwater prior to natural gas exploration.